CGIAR - Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD) - International Rice Research Institute (International Rice Research Institute, 2022)
The video introduces the CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD), its focus research areas, and target outcomes. AMD’s main goal is to transform food systems toward greater climate resilience by removing systemic barriers at community, national and regional levels to enable the scaling of existing and emerging technologies and practices.